Effectiveness Model of Village Funds to Measure Village Per-formance Through Economic Empowerment towards Prospeous Communities in East Java Coastal Areas - Ekasari, Ratna; Ratnawati, Tri; Sardjono, Sigit (International Journal of Engineering and Technology, 2018)
Rural communities that are part of the unitary state of the Republic of Indonesia need attention and the role of the government to improve the lives of its citizens to achieve a just and prosperous society according to the mandate of the Constitution. For this reason, the use of village funds which is a manifestation of government assistance for equitable development must be formulated and managed appropriately, transparently and accountable. This research method with a population of six villages in the coastal areas of East Java carried out by collecting data quantitatively namely the factual management of village funds based on histories from four research objects, which were analyzed based on the formulation of budget effectiveness. While the data obtained qualitatively obtained by questionnaires and interviews with respondents of the object of research, which is then analyzed to obtain the influence of independent variables on the dependent variable using the IBM SPSS Statistics software Ver.20. The results show that: quantitatively village budget management can be said to have effective assessment criteria, which is indicated by the percentage value above the specified effectiveness threshold. Whereas qualitatively it was found that the Village Fund variable did not show a positive and significant effect on the variables of budget effectiveness. Village Program variables do not show a positive and significant impact on the variable effectiveness of the budget. The Program Urgency variable does not show a positive and significant impact on budget effectiveness variables. The Program Implementation variable shows a positive and significant effect on the variable of budget effectiveness. Monitoring and Reporting variables show a positive and significant influence on budget effectiveness variables. Furthermore, the Budget Effectiveness Model is formulated which will be used as a reference in using village funds for the development and welfare of coastal communities in East Java.Â Â